Social Capital And Food Security Of Poor Households In Watersheds During The Covid-19 Pandemic - Meyzi Heriyanto; Khairul Anwar; Ismandianto; Ruzikna; Mashur Fadli; Yusmar Yusuf (International Journal of Educational Research & Social Sciences, 2021)
Poor Household Research on Social Capital and Food Resilience (RTM) The socioeconomic imbalances of impoverished households in the Siak watershed area provide the backdrop for the execution of the 2020 Social Distancing and PSBB policies. The condition of the population in the Tanjung Rhu and Rumbai Pesisir Sub-Districts that has tested positive for Covid-19 is relatively low, but the potential for the rise and socio-economic gaps is substantial. This research sought to answer the following key question: How can social capital be mobilized to increase food security for poor households in the context of social distancing and PSBB policies in two Pekanbaru sub-districts? Social participation and social capital theory can provide answers to this topic. The goal of this study was to look at the state of social capital and the possibilities for enhancing food security for disadvantaged families in the two Covid-19 in the year 2020: (1) The level of public trust in working together to strengthen food security during the implementation of social distancing and PSBB policies; (2) The level of a family trust in working together to strengthen food security during the implementation of social distancing and PSBB policies; (3) The benefits of formal and informal social networks in dealing with Social Distancing and PSBB; (4) The benefits of socialization medium for formal government and informal regulations fo? The following are the findings of the research given in this paper: To begin with, this PSBB policy influenced the river flow resilience of impoverished households in Pekanbaru City’s Tanjung Rhu and Meranti Pandak villages. Second, the components of social capital that were significantly related to community and household trust in establishing relationships without mutual suspicion, household trust in being able to maintain a sustainable environment, and in dealing with the impact of the implementation of Covid 19 after the PSBB’s enactment. Third, social capital can be established and improved at the community level in the form of social institutions that help improve food security in poor communities.